Effectiveness of Criminal Sanctions Against Union-Busting Actions by Media Companies - Syifadilla Subagyo Putri; Kayus Kayowuan Lewoleba (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This research explores the enforcement of criminal sanctions against union-busting practices in Indonesia, with a particular focus on the conflict between the CNN Indonesia Workers’ Solidarity (SPCI) and PT. CNN Indonesia. Employing a juridical-normative approach, the study reviews legal frameworks such as Law No. 21 of 2000 on Trade Unions and the Indonesian Criminal Code, while drawing comparisons with labor court rulings in Belgium, Germany, and France. The findings reveal that, although Indonesia’s legal system formally classifies union busting as a criminal act, its implementation remains ineffective due to the dominance of civil or bipartite settlements that rarely impose real sanctions. The research emphasizes the need for stronger institutional commitment and a more proactive role from law enforcement bodies to safeguard workers’ rights and ensure corporate accountability. Strengthening these measures will help harmonize Indonesia’s labor law with international standards promoted by the International Labour Organization (ILO).